Synthesis, physicochemical properties and electrochemical study of new lower valence vanadium (IV)-substituted molybdo-phosphate. (2022) - El Arrouji, I.; Oulmekki, A.; Taoufik, M.; Lefebvre, F.; Toyir, J.
Abstract: Novel vanadium (IV)-substituted molybdo-phosphates were prepared by self-assembly of vanadyl sulfate and mono-phosphomolybdic anions. Morphology and structure of the phosphate compounds was analyzed by Scanning electron microscopy (SEM), X-ray diffraction, Infrared spectroscopy (FT-IR) and Raman techniques. Chemical effect of molybdenum substitution by vanadium on the optical properties of phosphate compound was studied by UV–Vis spectroscopy and Cyclic Voltammetry was performed to follow the change in electrochemical behavior. X-ray diffraction exhibited that the overall structure was exchanged from triclinic (P-1) to cubic (Pn-3 m) after tetra-vanadium addition. The FT-IR and Raman results revealed that the keggin structure of V IV -POMs salts was preserved. Moreover, the cobalt introduced into K5 PMo11 V IV O40 phosphate significantly improved its optical property. The Co2.5 PMo11 V IV O40 displayed a quasi-reversible electrochemical behavior, which is beneficial towards desired applications using redox process-based systems.